Malnutrion and Associated Factors of Aboriginal Preschoolers in Gua Musang, Kelantan, Malaysia - Geik, Oui Pek; Sedek, Razalee; Awang, Ahmad Faris (Pakistan Journal of Nutrition, 2016)
Aboriginal children are known as one of the communities that engaged the highest prevalence of malnutrition in Malaysia for ages. The study was participated by 256 (131 males and 125 females) aboriginal preschooler aged one to six years from Gua Musang, Kelantan. This study attempts to determine the current prevalence of malnutrition and to identify the possible factors that may be associated with malnutrition among the subjects. This cross-sectional study was carried out between September to December 2014 at three aborigines’ settlements. Socio-demographic and economic status information, health history and anthropometric measurement of the participants were obtained and all the subjects were screened for presence of soil-transmitted helminths (STH). Current study revealed that the prevalence of underweight and stunted was 45.3 and 76.2%, respectively. From the analysis, there was no significant associated factors between demographic, socioeconomic, health history and personal hygiene with underweight (p>0.05). However, binary logistic regression confirmed that the significant factors contribute to stunting were household monthly income (<RM520) (p<0.01), number of siblings (>5) (p<0.01) and gender (male) (p<0.01). The current prevalence of malnutrition is still a major concern for public health with lower family monthly income and is the main factors that contribute to stunting. Hence, government should consider revising health strategies to overcome these issues in order to provide a better future for these children to survive.